2022
DOI: 10.1111/jdi.13776
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D status and diabetic foot in patients with type 2 diabetes mellitus

Abstract: Aims/Introduction To assess the association between vitamin D and diabetic foot (DF) in patients with type 2 diabetes mellitus (T2DM), in order to summarize clinical evidence in the prevention and treatment of DF. Materials and methods Between January 2012 and December 2019, a total of 1,721 hospitalized patients with type 2 diabetes mellitus were continuously enrolled in West China Hospital, Sichuan University, and divided into DF and non‐DF groups according to whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The observed correlation between vitamin D deficiency and DM has received a lot of attention in recent years. 21 Tang et al 22 found that the vitamin D levels in the DF group were significantly lower than that in the non-DF group. Dai et al 23 involving 51 patients investigated the relationship between 25-OH-vitamin D and DFU, and the results showed that 25-OH-vitamin D levels in DFU group were significantly lower than non-DFU group.…”
Section: Discussionmentioning
confidence: 98%
“…The observed correlation between vitamin D deficiency and DM has received a lot of attention in recent years. 21 Tang et al 22 found that the vitamin D levels in the DF group were significantly lower than that in the non-DF group. Dai et al 23 involving 51 patients investigated the relationship between 25-OH-vitamin D and DFU, and the results showed that 25-OH-vitamin D levels in DFU group were significantly lower than non-DFU group.…”
Section: Discussionmentioning
confidence: 98%
“…A total of 12 studies reported between 2013 and 2022 satisfied the inclusion criteria for the meta‐analysis among the 573 distinctive reports. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 This meta‐analysis study included 7586 subjects with diabetes mellitus at the beginning of the study; 1565 were using diabetic subjects with foot ulcer wounds, and 6021 were non‐ulcerated diabetic subjects. All studies evaluated the association between vitamin D deficiency and diabetic foot ulcer wounds in diabetic subjects.…”
Section: Resultsmentioning
confidence: 99%
“…-3 of 8 mutual relationship between vitamin D levels and DFU, reporting that vitamin D may represent a risk factor for DFU, which, in turn, may determine a worsening of vitamin D levels. 27 On the other hand, PTH levels have never been investigated in people with DFU and OM. Our findings hence contribute to the definition of PTH as a biomarker of chronic OM in diabetic patients with DFU.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be related to the high rate of vitamin D deficiency/insufficiency in patients with diabetes 26 . Moreover, a recent study investigated the mutual relationship between vitamin D levels and DFU, reporting that vitamin D may represent a risk factor for DFU, which, in turn, may determine a worsening of vitamin D levels 27 . On the other hand, PTH levels have never been investigated in people with DFU and OM.…”
Section: Discussionmentioning
confidence: 99%